Dynamic Alterations in the Gut Microbiota of Collagen-Induced Arthritis Rats Following the Prolonged Administration of Total Glucosides of Paeony - Peng, Jine; Lu, Xuran; Xie, Kaili; Xu, Yongsong; He, Rui; Guo, Li; Han, Yaxin; Wu, Sha; Dong, Xuerong; Lu, Yun; Liu, Zhengyue; Cao, Wei; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Rheumatoid arthritis is a common autoimmune disease linked to chronic inflammation. Dysbiosis of the gut microbiota has been proposed to contribute to the risk of RA, and a large number of researchers have investigated the gut–joint axis hypothesis using the collagen-induced arthritis rats. However, previous studies mainly involved short-term experiments; very few used the CIA model to investigate changes in gut microbiota over time. Moreover, previous research failed to use the CIA model to carry out detailed investigations of the effects of drug treatments upon inflammation in the joints, hyperplasia of the synovium, imbalance in the ratios of Th1/Th2 and Th17/Treg cells, intestinal cytokines and the gut microbiota following long-term intervention. In the present study, we carried out a 16-week experiment to investigate changes in the gut microbiota of CIA rats, and evaluated the modulatory effect of total glucosides of paeony, an immunomodulatory agent widely used in the treatment of RA, after 12 weeks of administration. We found that taxonomic differences developed in the microbial structure between the CIA group and the Control group. Furthermore, the administration of TGP was able to correct 78% of these taxonomic differences, while also increase the relative abundance of certain forms of beneficial symbiotic bacteria. By the end of the experiment, TGP had reduced body weight, thymus index and inflammatory cell infiltration in the ankle joint of CIA rats. Furthermore, the administration of TGP had down-regulated the synovial content of VEGF and the levels of Th1 cells and Th17 cells in CIA rats, and up-regulated the levels of Th2 cells and Treg cells. The administration of TGP also inhibited the levels of intestinal cytokines, secretory immunoglobulin A (SIgA) and Interferon-γ (IFN-γ). In conclusion, the influence of TGP on dynamic changes in gut microbiota, along with the observed improvement of indicators related to CIA symptoms during 12 weeks of administration, supported the hypothesis that the microbiome may play a role in TGP-mediated therapeutic effects in CIA rats. The present study also indicated that the mechanism underlying these effects may be related to the regulation of intestinal mucosal immunity remains unknown and deserves further research attention.